Neuro-radiology: a new gold standard investigation for management of central nervous system tuberculosis - Gautam, Vinod (International Journal of Medicine, 2016)
Treatment of CNS TB is challenging due to lack of specific biochemical tests and inability to get the pathological sample from deeply located eloquent areas of CNS without causing any neurological deficit. Moreover, it is unnecessary to operate for biopsy in a patient who has presented with a very small granulomatious lesion in brain or spinal cord. In such as situations neuro-radiology helps in managing CNS TB and it may be the only source of establishing diagnosis and evaluating treatment response.Role of radiological investigation has expanded from the initial diagnosis to the therapeutic interventions. In some Muli-drug- resistant (MDR) CNS TB cases, Stereotaxy or USG or CT guided biopsy helps in obtaining pathological sample and drug sensitivity testing. A regular clinical and neuro-radiological follow-up is mandatory during the entire course of anti tuberculous therapy to take prompt decisions to change ATT and to reduce morbidity and mortality associated with CNS TB.